The Muslim South and beyond - Tan, Samuel K. (University of the Philippines Press, 2010)
These essays are conveniently arranged from general to specific issues of the Mindanao conflict and the central relevance of the Muslim South to the problem. Because of its global ideological character, the first essay gives context to the Bangsamoro struggle which had received initial and substantial support from Libyan President Muammar Ghadafi as author of The Green Book which expounds the "Third International Theory."